Dynamis of Healing : Patristic Theology and the Psyche - Chaudhari, Pia Sophia (Orthodox Christianity and contemporary thought., 2019)
This book explores how traces of the energies and dynamics of Orthodox Christian theology and anthropology may be observed in the clinical work of depth psychology. Looking to theology to express its own religious truths and to psychology to see whether these truth claims show up in healing modalities, the author creatively engages both disciplines in order to highlight the possibilities for healing contained therein. Dynamis of Healing elucidates how theology and psychology are by no means fundamentally at odds with each other but rather can work together in a beautiful and powerful synergia to address both the deepest needs and deepest desires of the human person for healing and flourishing.